Investigation of tetracycline residues in poultry meat samples from Dhaka city by high-performance liquid chromatography - Nargis Parvin; Mohammad Shoeb; Nilufar Nahar; Rafiza Islam (Institut Teknologi Bandung, 2022)
The objective of the study was to quantify tetracycline (TCs) i.e., oxytetracycline (OTC), tetracycline (TC) and chlortetracycline (CTC) residues in thirty poultry meat samples (n = 30) collected from the local market and super shop around the Dhaka University campus during May 2019 to January 2020. Three samples were collected from each of ten locations. All samples were extracted by Quick, Easy, Cheap, Effective, Rugged and Safe (QuEChERS) method. Samples were analyzed by reversed-phase High-Performance Liquid Chromatograph equipped with Photo Diode Array Detector (LC-PDA) and a reported method was validated with good linear correlation coefficients of standards and matrix-matched calibration curves with r2=1.00, 0.99, 0.99 and r2= 0.99, 0.99,0.99 in the linearity range of 0-10 µg/kg for OTC, TC and CTC, respectively. The limit of detection (LOD) and limit of quantification (LOQ) for OTC, TC, and CTC were 1.05, 1.17, and 1.09 μg/kg and 3.15, 3.51 and 3.27 μg/kg, respectively. Accuracy that is expressed by the recovery percentages were calculated at two different concentrations (2.5 and 5 μg/kg) were 91 and 100%, 102 and 100%, and 106 and 100% for OTC, TC, and CTC, respectively. Intra-day (n=3) and inter-day (n=9, 3 days) precision data were under 10% for all sample matrixes. Standard deviations were calculated ±0.06, ±0.11 and ±0.03 and precision (expressed by RSD%) were found 5.57, 9.14 and 2.35%, respectively for OTC, TC and CTC. The HPLC-PDA method is affordable for screening of large number meat samples for residual antibiotics in biological matrices by any laboratories. The method is also cheaper in comparison with LC-MSMS. Analysis of real 30 poultry meat samples showed that the tetracyclines residues were below the quantification limit in all samples.